Determination of Cultivation Method Based On the Quality of Seaweed (Kappaphycus alvarezii) in Sumenep District - Wulandari, Siska Ayu; Setyaningsih, Sri; Rohmah, Alissa Nazilatur; Isdiantoni, Isdiantoni (Science Education and Application Journal, 2023)
The planting method greatly affects the growth and carrageenan content of Kappaphycus alvarezii seaweed. In addition, the planting method will also affect the physico-chemical conditions of the waters which are closely related to the growth of K. alvarezii. This study aims to determine the appropriate method of seaweed cultivation so that it can be used as a reference for K. alvarezii farmers to pay more attention to appropriate and appropriate cultivation methods in cultivating K. alvarezii so as to improve the quality of seaweed. This study begins with observations at the sampling location, taking water samples and samples of K. alvarezii seaweed. The research data was processed using SPSS (Statistical Product and Service Solution) version 16.0 software with analysis of variance (One Way ANOVA) to obtain parameters that affect the quality of seaweed so that the appropriate planting method can be determined. The results obtained from this study, the appropriate method for planting K. alvarezii in Palasa using a floating raft, in Lobuk and Padike using the bottom method, while in Tonduk using the long line method.